Pengaruh Produk Domestik Regional Bruto (PDRB) dan Upah Minimun Terhadap Realisasi Penanaman Modal Asing (PMA) di Kabupaten/Kota Kalimantan Timur Tahun 2017-2023 - Maysi Clara Puspita; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Gross Regional Domestic Product (GRDP) and Minimum Wage on the realization of FDI in five districts / cities in East Kalimantan during the period 2017-2023. The method used is a quantitative approach with panel data and multiple linear regression analysis using Eviews 9 software. The test results show that the best model is the Common Effect Model (CEM). Partially, the GRDP variable has a positive and significant effect on FDI realization, while the minimum wage variable has no significant effect. Simultaneously, both independent variables have a significant effect on FDI. The coefficient of determination (Adjusted R²) of 82.5% indicates that variations in FDI can be explained by GRDP and MSE. This finding confirms the importance of encouraging regional economic growth to attract more foreign investment, as well as considering the balance between labor cost incentives and labor welfare.